What is the association of hypothyroidism with risks of cardiovascular events and mortality? A meta-analysis of 55 cohort studies involving 1, 898, 314 participants. Issue 1 (December 2017) - Ning, Yu; Cheng, Yun J.; Liu, Li J.; Sara, Jaskanwal; Cao, Zhi Y.; Zheng, Wei P.; Zhang, Tian S.; Han, Hui J.; Yang, Zhen Y.; Zhang, Yi; Wang, Fei L.; Pan, Rui Y.; et al.
Abstract Background Whether hypothyroidism is an independent risk factor for cardiovascular events is still disputed. We aimed to assess the association between hypothyroidism and risks of cardiovascular events and mortality. Methods We searched PubMed and Embase from inception to 29 February 2016. Cohort studies were included with no restriction of hypothyroid states. Priori main outcomes were ischemic heart disease (IHD), cardiac mortality, cardiovascular mortality, and all-cause mortality. Results Fifty-five cohort studies involving 1, 898, 314 participants were identified. Patients with hypothyroidism, compared with euthyroidism, experienced higher risks of IHD (relative risk (RR): 1.13; 95% confidence interval (CI): 1.01–1.26), myocardial infarction (MI) (RR: 1.15; 95% CI: 1.05–1.25), cardiac mortality (RR: 1.96; 95% CI: 1.38–2.80), and all-cause mortality (RR: 1.25; 95% CI: 1.13–1.39); subclinical hypothyroidism (SCH; especially with thyrotropin level ≥10 mIU/L) was also associated with higher risks of IHD and cardiac mortality. Moreover, cardiac patients with hypothyroidism, compared with those with euthyroidism, experienced higher risks of cardiac mortality (RR: 2.22; 95% CI: 1.28–3.83) and all-cause mortality (RR: 1.51; 95% CI: 1.26–1.81). Conclusions Hypothyroidism is a risk factor for IHD and cardiac mortality. Hypothyroidism is associated with higher risks of cardiac mortality and all-cause mortality compared with euthyroidism in the general public or in patients with cardiac disease.